Correlation between antimicrobial resistance and virulence genes in Klebsiella pneumoniae isolates from Egypt - Nasma Maged Elemary; Mohamed Mahrous Emara; Amin Abd Elhady Tahoun; Ramadan Ahmed Eloomany (Journal of the Pakistan Medical Association, 2023)
Objective: To genotypically assess the relationship between certain resistance and virulence determinants. Method: The cross-sectional study was conducted at Kafrelsheikh University, Egypt, from March 2019 to May 2021, and comprised pathological samples, like blood, sputum, urine, vaginal swabs and wound swabs, that had been taken from patients who had never received treatment. The sample were collected from Kafrelsheikh and Mansoura University hospitals, and Klebsiella pneumoniae isolates were obtained. Resistance and virulence determinants were tested phenotypically. Uniplex polymerase chain reaction was used to evaluate the presence of several resistanceaccompanied genes and virulence genes in the isolates. Disc diffusion method was used to assess the isolates’ susceptibility in accordance with the Clinical and Laboratory Standards Institute criteria for identifying diverse resistance patterns. Results: There were 23 isolates from 16 patients. Of the tested isolates, 22(95.65%) showed drug resistance; 19(82.6%) had multidrug resistance, and 3(13.04%) had extensive drug resistance. There was no case of pan drug resistance. CTX-M-15, NDM, CTX-M-1, VIM-1 and qnr B genes were detected in 14(60.86%), 13(56.5%), 6(26.08%), 6(26.08%) and 6(26.08%) isolates, respectively. Moreover, 6(26.08%) isolates exhibited extended-spectrum beta-lactamase producers, and 12(52.17%) of such isolates contained both CTX-M-1 and CTX-M-15 genes, 6 and 33.3% contained CTX-M-1, CTXM- 15 and fox genes. Type 3 fimbriae adhesin mrkD and mucoviscosity regulatory gene uge were found in the tested isolates. However, gene of iron uptake system kfu was found in 8(34.78%) isolates, and increased serum survival protein is and mucoviscosity accompanied gene magA were detected in 3(13.04%) isolates. A direct correlation was found among 5 from 8 Klebsiella pneumoniae virulence genes and antimicrobial resistance genes. Conclusion: There was a direct correlation between the existence of virulence factors and resistance to antimicrobials. Keywords: Lactamase, Klebsiella pneumoniae, Anti-bacterial, Virulence, Bacterial, Genes.